Pengaruh Model Pembelajaran Role Playing Terhadap Hasil Belajar Siswa - Syinta Rahman; Hamka Hamka; Yusuf Yusuf (Mathematics Education Study Program, 2025)
This study aims to determine the influence of the Role Playing learning model on the learning outcomes of MAN 2 Bone students. The type of research used is the Type of Experimental Research with a Quantitative approach. The data processed is a Pre Test and Post Test given to all students of class X.6 MAN 2 Bone. The data collection method in this study is Test Instruments. The data was processed with instrument tests in the form of Question Difficulty Level Test and Question Differentiation Test, and to answer the Research Hypothesis, a Descriptive Statistical Test and an Infernal Statistical Test were carried out using a t-Test. Based on the acquisition of research results and existing data, the researcher can conclude that the Role Playing Learning Model has a positive effect on the learning outcomes of Economics students in class X.6 MAN 2 Bone. This can be proven from the results of the hypothesis test that has been carried out, t Count > t table or 11,373 > 2.03224, then Ho is rejected and H1 accepted.